2021
DOI: 10.1186/s12961-021-00738-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a guideline on sexual and reproductive health of breast cancer survivors in Iran: a mixed methods study protocol

Abstract: Background Sexual and reproductive health problems significantly decrease quality of life in survivors of breast cancer. The best approach is to provide services according to evidence-based guidelines developed based on their practical context. Here, we aim to develop and validate a guideline on the sexual and reproductive health of breast cancer survivors in Iran. Methods The guideline will be developed and validated using an exploratory sequentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, the results should be cautiously considered as the sexuality items were calculated from a small number of patients (11 patients for the sexual functioning scale and 13 patients for the endocrine sexual functioning scale) because most of the patients refused to answer these questions and felt that sexuality items were upsetting and intrusive. A trial on Iranian patients found that both the patients and the therapist were reluctant to talk about sexual health, although it was deteriorated tremendously in breast cancer patients compared to healthy women [26]. This trial proposed the requirement of valid clinical guidelines to provide suitable evidence-based care for sexual health in breast cancer cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results should be cautiously considered as the sexuality items were calculated from a small number of patients (11 patients for the sexual functioning scale and 13 patients for the endocrine sexual functioning scale) because most of the patients refused to answer these questions and felt that sexuality items were upsetting and intrusive. A trial on Iranian patients found that both the patients and the therapist were reluctant to talk about sexual health, although it was deteriorated tremendously in breast cancer patients compared to healthy women [26]. This trial proposed the requirement of valid clinical guidelines to provide suitable evidence-based care for sexual health in breast cancer cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…During breast cancer treatment, addressing sexual problems is not a priority. Both patient and therapist avoid talking about sexual concerns due to embarrassment, lack of privacy, time, or required skills [ 23 ]. Furthermore, in most Asian countries, including Iran, sexual issues are considered as taboo and talking about these issues is associated with feelings of shame and guilt.…”
mentioning
confidence: 99%